PEMANFAATAN BUNYI BAHASA DALAM SERAT WULANG REH KARYA PAKUBUWANA IV (KAJIAN STILISTIKA) - Muhammad Arikunto Wibowo; Soediro Satoto; Sumarlam . (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2017)
The use of language in Serat Wulang Reh created by Pakubuwana IV, especially related to the utilization of the sounds of language and choice of words. The problems examined this research is how to use the sounds of language in Serat Wulang Reh created by Pakubuwana IV? Data is data write in the form of fragments of the text in which there is the utilization of the sounds of language and choice of words. Data source is the document that Serat Wulang Reh created by Pakubuwana IV consisting of 283 stanzas version of Drs. Darusuprapto published by CV. Citra Jaya, Surabaya in 1982. The data was collected using methods see and record. Data were analyzed using methods distributional and unified method. The process of data analysis using steps or by components: reduction, presentation, verification and drawing conclusions. Preliminary results of this study identified that the utilization of the sounds of language includes purwakanthi swara (assonance), purwakanthi literature (alliteration), purwakanthi lumaksita. The created by Pakubuwana IV using words arkhais including ancient Javanese language diversity. From the use of the language sounds, Pakubuwana IV in his harness purwakanthi swara (assonance) consists of a repetition of vowel [a], [i], [u], [e], [ê], [o], purwakanthi literature (alliteration) consists of a repetition of consonant consonant [b], [d], [g], [h], [j], [k], [l], [m], [n], [ng], [p], [r], [s], [t], [w] and [y], purwakanthi lumaksita ie repetition of syllables and word repetition is productive which makes Serat Wulang Reh as characteristics.